Mechanisms of fatigue crack growth in Ti-6Al-4V alloy subjected to single overloads. (August 2021) - Neto, D.M.; Borges, M.F.; Antunes, F.V.; Jesus, J.
Highlights: FCG is predicted numerically in CT specimens of Ti-6Al-4V alloy. The specimens were submitted to single tensile overloads. Cyclic plastic deformation is assumed to be the main damage mechanism. Crack tip plastic strain is assumed to be the driving force. Closure, partial closure, blunting and material hardening effects are included. Crack closure is responsible for the effect of overloads on FCG rate behaviour. The residual stresses ahead of crack tip are not affected by the contact of flanks. Abstract: The relative importance of crack closure and residual stresses on fatigue crack growth (FCG), which is controversial, is studied here. FCG is predicted numerically in CT specimens of Ti-6Al-4V alloy submitted to single overloads, assuming that crack tip plastic strain is the driving force. The numerical procedure, which includes the effects of crack tip blunting, material hardening, crack closure and partial crack closure, was found to be very robust and to give correct trends. The high strength material studied showed relatively small overload affected zones (<0.5 mm), which is even more pronounced under plane strain conditions. The comparison of numerical results with and without contact of crack flanks showed that crack closure is responsible for the effect of overloads on FCG rate behaviour, while the effect of residual stresses is not relevant for the material studied. The transient behaviour obtained after an overload is unattainable without considering the contact of the crack flanks.